Perwujudan Profil Pelajar Pancasila melalui Problem Based Learning pada Pembelajaran IPA di SMPN 37 Semarang - Rima Handayani; Ipah Budi Minarti; Eko Retno Mulyaningrum; Endang Sularni (Departement of Mathematics Education, 2023)
The development of the world of education is currently leading to a student-centered learning process. The Merdeka Curriculum was developed as a curriculum framework that is more flexible, while also focusing on essential material and developing the character and competence of students. The Pancasila Student Profile is an effort to be able to lead individuals to a level of understanding, behavior, character based on Pancasila values. The strategy for developing the Pancasila Student Profile is carried out through integration in formal education activities through intracurriculars, one of which is the PBL model. Science learning is learning that has the goal of deepening understanding of a concept. This study aims to analyze the embodiment of the Pancasila Student Profile through Problem Based Learning in Science Learning at SMPN 37 Semarang. This type of research is descriptive qualitative with research subjects being students of class VII A SMP Negeri 37 Semarang. The sampling technique in this study is non-probability sampling. Data analysis in this study is a narrative analysis, with the instrument observation sheet. The results showed that the embodiment of the Pancasila Student Profile through Problem Based Learning in Science Learning at SMPN 37 Semarang can be applied well. From all aspects of the Pancasila Student Profile there is a connection with the syntax of the PBL learning model starting from giving apperceptions, discussions, presentations, to conducting evaluations. Then the Problem Based Learning learning model can realize aspects or dimensions of Pancasila Student Profiles for SMPN 37 Semarang students.